Practice patterns of bupropion co-prescription with antipsychotic medications. Issue 4 (3rd October 2022) - Gautam, Mohan; Patel, Shivali; Zarkowski, Paul
Abstract: Objective: Bupropion is one of the few medications with an FDA indication for smoking cessation. This is of particular significance due to the high co-morbidity of tobacco use disorder in patients with schizophrenia spectrum and other psychotic disorders. We sought to determine whether historical suggestions of bupropion's pro-dopaminergic activity lead prescribers to withhold bupropion in populations receiving antipsychotic medications. Methods: The prevalence in clinical practice of the combination of bupropion and 10 antipsychotic formulations was determined by a computer review of the Genoa Healthcare database for all prescribers at 10 participating community mental health centers. Actual prevalence was compared with expected prevalence using the test of proportions. A Bonferroni correction for multiple comparisons was included. Results: Clozapine, p = 0.0004, and the microsphere formulation of risperidone, p = 0.0045, were prescribed with bupropion significantly less often that chance. None of the other eight antipsychotic formulations were prescribed significantly differently than chance. Conclusions: The co-prescription of bupropion and antipsychotic medication may be affected by historical misconceptions regarding bupropion's purportedly pro-dopamine properties. Viable options for the treatment of tobacco use disorder should not be discounted prematurely in patients with schizophrenia spectrum and other psychotic disorders. We suggest further study on the safety and efficacy of the combination of bupropion and antipsychotic medication is needed.